Probabilistic Compensation Criteria - Polinsky, A. Mitchell (Quarterly Journal of Economics, 1972)
I. Introduction, 407. — II. The multiple-change approach, 409. — III. A general probabilistic framework, 412. — IV. The quasi-Paretian criterion, 418. — V. Concluding remarks, 423.